THE USE OF SEAWORM MEAL IN MATURATION DIET AS PARTIAL SUBSTITUTION OF FRESH DIET FOR POND REARED TIGER SHRIMP BROODSTOCK - Asda Laining; Usman Usman; Rachman Syah (Indonesian Aquaculture Journal, 2014)
The purpose of this experiment was to evaluate the effects of using seaworm meal in artificial diet as partial substitution of freshfeed for maturation of tiger shrimp. This experiment started by growing-out tiger shrimp with initial weight around 60 g for four months until reaching maturation phase where shrimp weight were over 90 g for female. Tiger shrimp was selected and stocked into 10 ton concrete tank with stocking density of 50 shrimps with ratio of female : male of 1:1. Dietary treatments were different levels of seaworm meal at 0% (SW0), 10% (SW10) and 20% (SW20). SW0 was positive control without seaworm meal but breeder was fed with frozen seaworm. Test diets were fed as a combination of 60% test pellet and 40% fresh feed. Artificial insemination was carried out for all females before ablation to obtain fertile eggs. Results showed that after ablation, number of female matured was highest in group fed SW10 (13 breeders) and the lowest in female fed control group (7 breeders). Number of female spawned was also highest in female fed SW10 and the lowest was in positive control. Fecundity was very low in all treatments ranged from 12,000-79,700 eggs/spawn. Even though female bearing spermatophore through insemination, number of spawning hatched was very low, only three spawned in each of SW0 and SW10 and two spawned in SW20. Based on number of breeders matured and spawning rate, breeder fed with SW10 gave better performance than other two diets. Technique of artificial insemination needs to be improved to increase the number of fertile eggs.